Инмозь сузись писпу: сказка : на удм. и венг. яз. / Э. Бенэдэк ; худ. А. Щёткин - Бенэдэк Элэк (ООО ПКФ "Буква", 2012)
Экземпляры: б/ф-3 (20140114) / Инвентарный номер: 33740 / Цена: 100.00 / Авт.знак: Б 46 / ББК: 84(4Вен)